Dexmedetomidine addition to local anesthetic mixture for peribulbar anesthesia in strabismus surgery - Ahmed F. Gabr; Badry M. Badry; Mohammed H. Rabea (Journal of the Egyptian Ophthalmological Society)
Aim To evaluate the effect of the addition of dexmedetomidine to the local anesthetic mixture for peribulbar anesthesia in strabismus surgeries. Methods A randomized controlled study included 58 patients who were divided into two groups, group І: included 29 patients who received peribulbar block by a mixture of local anesthetics only, and group II: included 29 patients who received peribulbar block by a mixture of local anesthetics with dexmedetomidine. All cases underwent preoperative full ophthalmic examination. The onset and duration of sensory block, onset and duration of motor block, hemodynamic parameters, sedation level, and duration of analgesia were assessed. Results The onset of sensory and motor block was shortened (P =0.021 and <0.001, respectively) and their duration was prolonged (P <0.001) and the duration of postoperative analgesia was significantly longer in the dexmedetomidine group (P <0.001). Dexmedetomidine group achieved higher sedation scores and lower intra and early postoperative pain scores (P 0.001 and <0.001, respectively) with higher levels of patient and surgeon satisfaction. Conclusion The addition of dexmedetomidine with the local anesthetic mixture for peribulbar anesthesia in strabismus surgeries accelerates the onset of anesthesia and akinesia of the globe and prolongs their duration. It extends the time to the first analgesic request and enhances the satisfaction of both patients and surgeons.